PERAN STRATEGIS MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN PRODUKTIVITAS KERJA KARYAWAN - Mahyarni Mahyarni; Astuti Meflinda (An-Nida', 2011)
Globalization is happening lately has a significant impact for organizational survival. Globalization has resulted in changes so quickly in the business, which requires organizations to be better able to adapt, have endurance, able to change direction quickly, and his attention to the consumer. Globalization can also bring danger, as well as an opportunity for the organization. In a business environment like this. Functions of Human Resource Management (HRM) with in the organization must be able to become a reliable partner for leadership in improving employee productivity. Because HR is a central factor in an organization. What ever the shape and purpose, the organization is based on a variety of visions for the benefit of man and in the implementation of the mission is managed and maintained by humans, Thus man is a strategic factor in all activities of the organization.